The potentials of the Southern & Eastern European countries in the process of the regionalization of the global supply chains using a q-rung orthopair fuzzy-based integrated decision-making approach. (September 2022) - Hashemkhani Zolfani, Sarfaraz; Krishankumar, Raghunathan; Pamucar, Dragan; Faruk Görçün, Ömer
Highlights: Presenting a new model of VIKOR method based on q-rung orthopair fuzzy sets. Presenting new strategies for regionalization of the global supply chains (GSC) Preparation of a set of criteria, for evaluation of regionalization of the chains GSC. Abstract: Recent challenges such as COVID 19 and the blockage of the Suez Channel have shown that the global supply chains (GSC) have extremely fragile structures. Hence, the GSCs have started to seek new strategies to be less affected. From this perspective, regionalization of the GSCs may be the best and most practical way to create more strength, well-operating, and robust supply chain systems. When a detailed literature review was performed, two severe and significant gaps were noticed. First is related to the methodological frame. The second gap is also concerned to the criteria used in the previous studies, as it is not clear how these criteria were identified and whether these criteria are suitable to the current real-life decision-making problems. The current paper aims to fill these gaps existing in the literatures. It examines the regionalization potentials of the GSCs and proposes an integrated MCDM framework based on the q-rung orthopair fuzzy sets. Also, it presents updated criteria set that can be commonly accepted. These criteria were identified by performing comprehensive fieldwork with highly experienced professionals with extensive knowledge of the GSCs and a detailed literature review to determine the criteria used in the previous works. The proposed model was applied to evaluate the potential of the southern and eastern European countries to be a manufacturing center for the GSCs. Then, a comprehensive sensitivity analysis performed for validating the proposed MCDM approach approves the proposed model's validity and efficacy by showcasing the close combat among the European countries.